2016
DOI: 10.7216/1300759920162310106
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Yarns For Thermoplastic Composites: Manufacturing Methods and Properties

Abstract: Günümüzde elyaf takviyeli termoplastik kompozit malzemeler yüksek dayanım ve geri dönüştürülebilme özelliklerinden dolayı yaygın şekilde kullanılmaktadır. Üstün avantaj sağlayan bu özelliklerinin yanında yüksek erime viskozitesi ve düşük ısıl dayanım gibi özellikler bu malzemelerin zayıf yönünü oluşturmaktadır. Termoplastik malzemelerin çalışma şartlarını zorlaştıran ve üretim maliyetlerini arttıran yüksek erime viskozitesi gibi problemlerin çözülmesi için güçlendirici elyaf ve matrisin katı halde karıştırılma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Thus, studies have shown increased efforts to convey various functionalities to textile fibers, such as electrical conductivity, which is critical for applications such as anti-static protection, electromagnetic interferences (EMI) shielding, sensors, textile electrode material for charge storage systems, or signal transfer [5]. Since textile polymers are largely insulating by nature, several approaches [6] exist on how to enhance the high conductivity of the textiles such as using thin metal wires or hybrid yarns [7] with metalcore in woven or knitted fabrics [8]. An alternative method is to coat the fibers, yarns, or fabrics with a thin metal layer or a conductive polymer [9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, studies have shown increased efforts to convey various functionalities to textile fibers, such as electrical conductivity, which is critical for applications such as anti-static protection, electromagnetic interferences (EMI) shielding, sensors, textile electrode material for charge storage systems, or signal transfer [5]. Since textile polymers are largely insulating by nature, several approaches [6] exist on how to enhance the high conductivity of the textiles such as using thin metal wires or hybrid yarns [7] with metalcore in woven or knitted fabrics [8]. An alternative method is to coat the fibers, yarns, or fabrics with a thin metal layer or a conductive polymer [9].…”
Section: Introductionmentioning
confidence: 99%